The Importance of Product Quality in Shaping Hotel Guest Satisfaction and Loyalty - GHOFUR, Abdul; LISTYORINI, Haniek (Journal of Tourism Economics and Policy, 2025)
As an industry that has a level of fierce competition, it is important for the hospitality industry to not only increase market share but also maintain customer loyalty through product quality and managing guest satisfaction. The research aims to test the influence of hotel product quality in creating satisfaction and loyalty as well as mediating guest satisfaction in fostering loyalty. The research was carried out by quantitative method by distributing questionnaires to hotel guests as many as 100 respondents. Data is processed with SMART PLS version 3. The results of the study show that the quality of hotel products has a positive and significant effect on guest satisfaction, guest satisfaction affects guest loyalty, product quality also positively has a direct influence on guest loyalty and guest satisfaction can mediate the influence of product quality on hotel guest loyalty.